Synthesis of 1-azaspiro[4.4]nonan-1-oxyls via intramolecular 1,3-dipolar cycloaddition - Khoroshunova, Yulia V.; Morozov, Denis A.; Taratayko, Andrey I.; Gladkikh, Polina D.; Glazachev, Yuri I.; Kirilyuk, Igor A. (Beilstein Journal of Organic Chemistry, 2019)
Sterically shielded nitroxides of the pyrrolidine series have shown the highest resistance to reduction. Here we report the synthesis of new pyrrolidine nitroxides from 5,5-dialkyl-1-pyrroline N-oxides via the introduction of a pent-4-enyl group to the nitrone carbon followed by an intramolecular 1,3-dipolar cycloaddition reaction and isoxazolidine ring opening. The kinetics of reduction of the new nitroxides with ascorbate were studied and compared to those of previously published (1S,2R,3′S,4′S,5′S,2″R)-dispiro[(2-hydroxymethyl)cyclopentan-1,2′-(3′,4′-di-tert-butoxy)pyrrolidine-5′,1″-(2″-hydroxymethyl)cyclopentane]-1′-oxyl (1).
Keywords: aldonitrone; 1,3-dipolar cycloaddition; pyrrolidine nitroxides; 1-pyrroline-N-oxide; sterically shielded nitroxide